A secure user authentication protocol using elliptic curve cryptography. (19th May 2019) - Kumari, Adesh; Yahya Abbasi, M.; Kumar, Vinod; Khan, Akber Ali
Abstract: Authentication is a significant security prerequisite for secure communications. However, most of identity assisted mutual authentication protocols are requiring of security verification, which is extremely impartment for cryptographic approach. The proposed protocol is a better identity based mutual authentication framework for two users over secure communication network. Further, paper shows the security analysis and compares with other related protocols in secure communication.